2017
DOI: 10.1021/acs.jpclett.7b03000
|View full text |Cite
|
Sign up to set email alerts
|

Aufbau Rules for Solvated Electron Precursors: Be(NH3)40,± Complexes and Beyond

Abstract: Tetra-amino beryllium complexes and ions, Be(NH), have a tetrahedral Be(NH) core with one, two, or three outer electrons orbiting its periphery. Our calculations reveal a new class of molecular entities, solvated electron precursors, with Aufbau rules (1s, 1p, 1d, 2s, 1f, 2p, 2d) that differ from their familiar hydrogenic counterparts and resemble those of jellium or nuclear-shell models. The core's radial electrostatic potential suffices to reproduce the chief features of the ab initio results. Wave function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(111 citation statements)
references
References 27 publications
7
92
1
Order By: Relevance
“…This observation is in harmony with the unique property of ammonia to solvate electrons . The addition of a fourth ammonia molecule leads to the pseudo‐spherical Be(NH 3 ) 4 complex which is clearly composed of a Be(NH3)42+ core and two “solvated” electrons orbiting around it in hydrogenic‐type (s, p, d, f, …) orbitals . This is largely due to its high N—H bond dipole: The NH 3 dipole moment is 2.5 times larger than that of PH 3 (1.518 vs. 0.606 D).…”
Section: Be(ah3)3mentioning
confidence: 57%
See 1 more Smart Citation
“…This observation is in harmony with the unique property of ammonia to solvate electrons . The addition of a fourth ammonia molecule leads to the pseudo‐spherical Be(NH 3 ) 4 complex which is clearly composed of a Be(NH3)42+ core and two “solvated” electrons orbiting around it in hydrogenic‐type (s, p, d, f, …) orbitals . This is largely due to its high N—H bond dipole: The NH 3 dipole moment is 2.5 times larger than that of PH 3 (1.518 vs. 0.606 D).…”
Section: Be(ah3)3mentioning
confidence: 57%
“…Phosphine creates similar complexes, but ammonia has strikingly different behavior. We recently observed that beryllium can make a novel type of chemical bonds when it reacts with four ammonia molecules creating a solvated electron precursor (SEP) . The 2s electron pair of Be is shifted from the metal to the periphery of the tetrahedral Be(NH 3 ) 4 complex.…”
Section: Introductionmentioning
confidence: 99%
“…In that sense these molecules are similar to the previously studied"solvated electron precursors" (SEPs), where an SEP is a complex that consists of M(L) n q+ core (M = metal, L = ligand) with one or few diffuse electrons. [42][43][44][45][46][47] Interestingly, SEPs populate atomic p-, d-, f-, and g-type orbitals in excited states. The exact Aufbau order introduced for the M(NH 3 ) 4 (M = Li, Na) SEPs is 1s, 1p, 1d, 2s, 2p.…”
Section: Introductionmentioning
confidence: 99%
“…42 The implementation of an augmented basis set on terminal H-atoms is critically important for the correct representation of their excited states. 43,44 Specifically, the M:cc-pVTZ, N/O:cc-pVTZ, H:d-aug-cc-pVTZ combination is proven to describe the excited electronic states of SEPs accurately and efficiently. 43,44 Similar to the SEPs the M@C 20 H 20 (M = Li, Na, Mg + ) populate higher angular momentum p-, d-, f-shaped orbitals in low-lying excited electronic states, hence can be recognized as "superatoms" .…”
Section: Introductionmentioning
confidence: 99%
“…The geometric and electronic features of the main group metal‐NO species are less studied in the literature. However, recently main group metal‐ligand systems have become more and more popular because of their versatile chemical bonding patterns . Specifically, Andrews et al studied linear LiNO, linear LiON, and side‐bonded Li[NO] species under density functional theory (DFT) .…”
Section: Introductionmentioning
confidence: 99%